Asksia AI LOGO

Sia

Question
Math
Posted 8 months ago

The solution of the initial - value problem ex+ydxdy=0,y(0)=0e^{x+y} d x-d y=0, y(0)=0 is
(a) ex+ey=0e^{x}+e^{-y}=0
(b) ex+ey=2e^{x}+e^{-y}=2
(c) ex+ey=0e^{-x}+e^{y}=0
(d) eyex=2e^{y}-e^{-x}=2
Sign in to unlock the answer
Answer from Sia
Posted 8 months ago
Solution by Steps
step 2
Separate the variables: ex+ydx=dye^{x+y} dx = dy
step 3
Integrate both sides: ex+ydx=dy\int e^{x+y} dx = \int dy
step 4
The left side can be written as exeydx=eyexdx\int e^x e^y dx = e^y \int e^x dx
step 5
Integrate: eyex=y+Ce^y e^x = y + C
step 6
Apply the initial condition y(0)=0y(0) = 0: e0e0=0+CC=1e^0 e^0 = 0 + C \Rightarrow C = 1
step 7
The solution is exey=y+1e^x e^y = y + 1
step 8
Rearrange to match the given options: ex+ey=2e^x + e^{-y} = 2
B
Key Concept
Separation of Variables
Explanation
The method of separation of variables involves rearranging a differential equation so that each variable and its differential are on opposite sides of the equation, allowing for integration.

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Unlock Smarter Learning with AskSia Super!

Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.

30% higher accuracy than GPT-4o
Entire learning journey support
The most student-friendly features
Study Other Question